2016
DOI: 10.1111/jocn.13183
|View full text |Cite
|
Sign up to set email alerts
|

‘Don't put the parent out’: parents' perspectives of being present during an inter‐hospital transfer

Abstract: There is a need to maximise the facilitation of parental presence in an Irish context through the introduction of guidelines to support staff involved in the transfer of an acutely ill child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…What differs in our study is that an increase in the number of hospital transfers predicted the likelihood of lower breastfeeding rates on discharge. Interhospital transfer is a known stressor for parents 15 and practice variations across neonatal units may contribute to such stress. Practice variations observed included different access policies, 16 lack of health professional knowledge of breastfeeding, variable availability of lactation support, 13,17 exposure to multiple carers and inconsistent and conflicting advice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…What differs in our study is that an increase in the number of hospital transfers predicted the likelihood of lower breastfeeding rates on discharge. Interhospital transfer is a known stressor for parents 15 and practice variations across neonatal units may contribute to such stress. Practice variations observed included different access policies, 16 lack of health professional knowledge of breastfeeding, variable availability of lactation support, 13,17 exposure to multiple carers and inconsistent and conflicting advice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The theory further classifies facilitators and inhibitors as personal, interpersonal, organizational, communal and societal (Chao et al, 2020). Studies are emerging showing that not only the patient suffers during multiple transitions, but also the family members as well (Karlsson et al, 2020; Masterson & Brenner, 2016; Oh et al, 2015). A recent qualitative study identified discharge facilitators after TBI rehabilitation such as adequate patient health, access to healthcare services, availability of family caregiver, attachment to home, commitment to loved one, possibility of transitional phase (e.g.…”
Section: Introductionmentioning
confidence: 99%